UPAYA MENINGKATKAN HASIL BELAJAR MURID MELALUI MODEL TEAMS GAMES TOURNAMENT (TGT) PADA MATERI KONJUNGSI DI UPT SDN SENDANGHARJO IV - Rofifah Nindya Mahalli; Sumadi; Sri Wahyuni (STKIP Subang, 2026)
This classroom action research aimed to improve the learning outcomes of fourth-grade students at UPT SDN Sendangharjo IV in the Indonesian language topic of conjunctions through the Teams Games Tournament (TGT) learning model. The study was motivated by the low learning outcomes of students, where only 6 of 28 students reached the Learning Achievement Criteria (KKTP) at the initial observation. This research followed the Kemmis and McTaggart model, comprising planning, acting, observing, and reflecting, and was carried out in two cycles. The subjects were 28 fourth-grade students. Data were collected through learning outcome tests and observation sheets, then analyzed descriptively and quantitatively. The results showed that the average score and classical mastery increased in every cycle, from 66.14 (21.43%) in the pre-cycle to 72.39 (35.71%) in Cycle I using Discovery Learning, and to 84.39 (89.29%) in Cycle II using TGT. Teacher and student activity also improved, reaching 96% and 92% respectively in the very good category in Cycle II. These findings indicate that the TGT model effectively improves student learning outcomes and engagement in learning conjunctions.